The effect of internal control system’s effectiveness on village government’s performance - Mulyani, Sri, Uskara, A.M, Mulyani, Sri, Akbar, Bahrullah,; Sudraja, . (Opción, 2019)
The present study aims to proof the effect(s) of the internal control system’s effectiveness on village government’s performance, measured through levels of fraudulent activities in village fund management. Data was analyzed using Structural Equation Model (SEM)-LISREL method. The result shows that the lower the internal control effectiveness is, the higher level of fraudulent activities in village fund management are; which may lead to low performance of village government. In conclusion, an effective internal control system plays a crucial role in reducing frauds in village fund management.